The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1039/c7ra07999k
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer investigation in a horizontal–vertical pulsed packed extraction column

Abstract: In this study, hydrodynamic parameters and the mass transfer coefficient were investigated in a pilot version of a horizontal-vertical pulsed packed extraction column using a toluene-acetone-water system. The effects of the operational parameters on the volumetric overall mass transfer coefficient and hydrodynamic parameters away from the flooding point were studied, and it was found that the volumetric overall mass transfer coefficient, mean drop size and disperse phase holdup were significantly affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The dispersion regime is characterized by a non‐uniform bubble size distribution and no bubble coalescence occurs. [ 99 ] At higher pulsing velocities, good mixing occurs and the external energy dissipation is even throughout the column. [ 7,104 ] The pulsing velocities in the dispersion regime prevent the accumulation of bubbles either above or below each perforated plate as turbulence stresses dominate over the bubble coalescence tendency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersion regime is characterized by a non‐uniform bubble size distribution and no bubble coalescence occurs. [ 99 ] At higher pulsing velocities, good mixing occurs and the external energy dissipation is even throughout the column. [ 7,104 ] The pulsing velocities in the dispersion regime prevent the accumulation of bubbles either above or below each perforated plate as turbulence stresses dominate over the bubble coalescence tendency.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported through experimental findings that the mass transfer performance enhances with an increase in the pulsing velocity. [49,[98][99][100] It is found that as the pulsing velocity increases, the degree of turbulence effect transmitted in the column is more. The mean bubble diameter is affected by the pulsing velocity, as the additional rigorous shear forces that are created by the increased pulsing velocity cause the collapse of the bigger bubble into smaller ones, hence increasing the interfacial area which increases k L a.…”
Section: Influence Of Pulsing Velocity On K L a In The Presence Of Na...mentioning
confidence: 99%
“…Solvent extraction is a technique for separation having broad applications in different industries such as the petroleum, metal salt extraction, wastewater purification, pharmaceutical, and nuclear industries. 1–11 Various types of liquid–liquid contactors have been developed, including columns, centrifugal extractors, and mixer-settlers in this respect over many years. 12–19 The contactors with internal moving parts have a lower capacity than convectional non-internal moving part contactors, though their extraction efficiency is high.…”
Section: Introductionmentioning
confidence: 99%
“…12–19 The contactors with internal moving parts have a lower capacity than convectional non-internal moving part contactors, though their extraction efficiency is high. 1,2 Hence, efforts have been made to expand the extractive columns lacking mixers or internal moving parts. Generally, criteria to choose a suitable contractor must be considered, including capacity, maintenance, protection, high efficiency under a broad range of operational conditions, process control, and cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation